Case report and literature review: Primary leiomyosarcoma of the penis - Hao, Yichang; Xia, Li; Lu, Min; Liu, Chenhong; Zhang, Fan; Yan, Ye; Huang, Yi; Zhang, Shudong (Frontiers in Surgery, 2023)
Background Leiomyosarcoma (LMS) is a malignant spindle-cell mesenchymal tumor originating from the smooth muscle cells, which mostly affects soft tissues and abdominopelvic organs over extremities. Primary LMS of the penis is a relatively uncommon mesenchymal tissue disease and a poorly understood condition. Case Report A 69-year-old man presented with a growing, painless mass protruding from the penis. The irregularly lobulated lump was roughly 3 cm × 2.5 cm, with a smooth surface, tough texture, distinct boundary, and no tenderness. It was determined to be a penile tumor during the preoperative radiological evaluation. The patient underwent resection of the penile mass, followed by extended resection in the second operation. The diagnosis of LMS was verified by pathological examination. During a 20-month follow-up, the patient made a smooth recovery and remained disease-free. Conclusion An immunohistochemical examination is essential for rendering this rare diagnosis. Radical excision of tumor lesions with negative cut margins is guaranteed to be the best treatment for primary penile LMS. Close follow-up should be provided due to the high rate of local recurrence.